فكرة التطور القانوني بين تبدّل القانون وتغيّر الواقع : دراسة تحليلية استخلاصية, لعنصر (المستقبل!) في القاعدة القانونية - محمد سليمان الأحمد (PROSPECTIVE RESEARCHES, 2023)
Law aims normally to coincide reality, else it would be useless. In the past, it was not easy to modify law provisions, jurists tried to apply them blindly, They tried to change reality to suit them. And in their interpretations to these provisions, they tended to presupposition. And when the spirit of these old laws had weakened, justice principles had been adopted to be applied with some flexibility. Since this method lead to give certain role in creating the legal basis, the legislator tend to promulgate the modified legislation. One may believe that whatever the statutes is prolonged in time, it would be more evaluated by people. This result may contradict the fact that the old statutes do not coincide the modern thoughts and life. So, to make a sort of balance, the legislator must realize an important element which is the Future, which provides flexible rules. Through it, the idea of legal development would be accomplished and completed.